2022
DOI: 10.3390/biomedicines10071727
|View full text |Cite
|
Sign up to set email alerts
|

DSCAM-AS1 Long Non-Coding RNA Exerts Oncogenic Functions in Endometrial Adenocarcinoma via Activation of a Tumor-Promoting Transcriptome Profile

Abstract: Accumulating evidence suggests that lncRNA DSCAM-AS1 acts tumor-promoting in various cancer entities. In breast cancer, DSCAM-AS1 was shown to be the lncRNA being most responsive to induction by estrogen receptor α (ERα). In this study, we examined the function of DSCAM-AS1 in endometrial adenocarcinoma using in silico and different in vitro approaches. Initial analysis of open-source data revealed DSCAM-AS1 overexpression in endometrial cancer (EC) (p < 0.01) and a significant association with shorter over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 74 publications
(107 reference statements)
0
3
0
Order By: Relevance
“…The overexpression of another lncRNA-DSCAM-AS1 is associated with higher expression levels of the prolactin gene (PRL) and estrogen receptor α (Erα), a more aggressive course of EC, and a shorter survival period of patients. The oncogenic role of DSCAM-AS1 is correlated with the blocking of miR-136-5p actions [ 50 , 51 ]. In other research, it has been shown that VPS9D1-AS1 can contribute to EC progression by binding to miR-520a-5p and promoting the expression of Baculoviral IAP Repeat-Containing 5 (BIRC5).…”
Section: The Role Of Lncrna In Endometrial Cancermentioning
confidence: 99%
“…The overexpression of another lncRNA-DSCAM-AS1 is associated with higher expression levels of the prolactin gene (PRL) and estrogen receptor α (Erα), a more aggressive course of EC, and a shorter survival period of patients. The oncogenic role of DSCAM-AS1 is correlated with the blocking of miR-136-5p actions [ 50 , 51 ]. In other research, it has been shown that VPS9D1-AS1 can contribute to EC progression by binding to miR-520a-5p and promoting the expression of Baculoviral IAP Repeat-Containing 5 (BIRC5).…”
Section: The Role Of Lncrna In Endometrial Cancermentioning
confidence: 99%
“…highlighted that DSCAM-AS1 interacts with nuclear ribonucleoprotein (hnRNPL) in BC cells, promoting tumor progression and inducing tamoxifen resistance (49). More recently, Yadav et al (50) demonstrated that progesterone also can induce expression of DSCAM-AS1 and its silencing mimics the effect of progesterone in impeding cell migration and invasion in PR + BC cells.…”
Section: Breast Cancer (Bc)mentioning
confidence: 99%
“…Additionally, original articles concentrated on different aspects of the biology of ncRNAs. Gargaun et al looked at the possible role of the lncRNA 44s2 and of 45-55 multiexon skipping as therapeutic strategies in Duchenne and Becker muscular dystrophies [6], while Treeck et al identified DSCAM-AS1, a lncRNA with oncogenic roles in endometrial adenocarcinoma, as witnessed by its association with a shorter overall survival of patients affected by this cancer and with the expression of both the endometrial tumor promotor gene prolactin (PRL) and the Estrogen Receptor α (ERα) [7].…”
mentioning
confidence: 99%